ANALISIS KOMPETENSI PEGAWAI ASN DALAM MENGGUNAKAN LAYANAN DIGITAL DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL (DISDUKCAPIL) KARAWANG - Ade Wasiah (MANAJEMEN DEWANTARA, 2026)
This research intends to analyze the level of technical competence among employees within the Population Registration Division of the Karawang Regency Population and Civil Registration Office in implementing digital public services and to identify the factors influencing it. This study applies a qualitative descriptive methodology through data collection via observation, in-depth interviews, and documentation. This study involved five informants consisting of employees of the Population Registration Division who were directly involved in the implementation of digital-based population administration services. Source triangulation was used as a validation method to strengthen the validity of the research results. Research shows that employees’ technical competence is generally in the adequate category, as employees demonstrate understanding of digital service systems, the ability to operate applications, accuracy in data input, and awareness of technical constraints affecting service effectiveness. Although most employees understand the workflow and functions of digital services, competency gaps remain, particularly among employees with low to moderate skills. Several obstacles were identified, including unstable internet connections, application errors, and limited socialization during system updates, all of which influence the speed and smoothness of service delivery. In terms of accuracy, employees have performed data verification adequately, although minor errors still require attention.